Imaging the photons during transmission of ions through glass capillaries. (29th January 2015) - Akram, N; Schuch, R
Abstract: Charged particles, in particular slow highly charged ions, can be guided through nanocapillaries in various insulating materials by self-organized charge patches. We present a technique for observing directly the formation of these patches in glass capillaries. It is based on imaging the emitted visible photons. We report here on tests with 4.5 keV Ar + -ions transmitted through straight and tapered borosilicate capillaries, using a highly sensitive digital camera. Simultaneously, the ions transmitted through the capillaries were detected. The number of emitted photons decreases by increasing the tilt angle of the capillary. The time evolution of emitted photons revealed a change of location of the charge patches during charging-up the capillary walls.